2021
DOI: 10.3201/eid2706.210465
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Evidence for Airborne Transmission of SARS-CoV-2 during Church Singing, Australia, 2020

Abstract: An outbreak of severe acute respiratory syndrome coronavirus 2 infection occurred among church attendees after an infectious chorister sang at multiple services. We detected 12 secondary case-patients. Video recordings of the services showed that case-patients were seated in the same section, up to 15 m from the primary case-patient, without close physical contact, suggesting airborne transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
126
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 8 publications
9
126
0
2
Order By: Relevance
“…Further, these values can serve as the basis for a detailed numerical analysis of airborne transmission under different settings 8,36 and the estimation of quanta 37,38 , where one quantum is defined as the minimum dose of infectious viruses causing an infection in 63.2% of susceptile persons 39 . It should be noted that in the course of the actual pandemic so far, numerous situations seem to be related to a high probability of aerogenic virus transmission, including choir rehearsals [15][16][17]40 . There is an overwhelming evidence of viable SARS-CoV-2 viruses in indoor air [2][3][4][5]41 .…”
Section: This Study (Particles/sec)mentioning
confidence: 99%
“…Further, these values can serve as the basis for a detailed numerical analysis of airborne transmission under different settings 8,36 and the estimation of quanta 37,38 , where one quantum is defined as the minimum dose of infectious viruses causing an infection in 63.2% of susceptile persons 39 . It should be noted that in the course of the actual pandemic so far, numerous situations seem to be related to a high probability of aerogenic virus transmission, including choir rehearsals [15][16][17]40 . There is an overwhelming evidence of viable SARS-CoV-2 viruses in indoor air [2][3][4][5]41 .…”
Section: This Study (Particles/sec)mentioning
confidence: 99%
“…Near immediate limitations on live musical performance were imposed, precipitated in part by the appearance of clusters of COVID-19 associated with several choirs around the world (Charlotte 2020;Miller et al 2020). A recent epidemiological study identified an outbreak where a chorister infected 12 church attendees seated >15 m away who had no close physical contact with the chorister, suggesting airborne transmission (Katelaris et al 2021). Concerns about the risks associated with playing woodwind and brass instruments resulted in the imposition of similar restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, majority of researchers have focused on coughing and sneezing in their studies. 11 15 It is also known that asymptomatic patients, who rarely cough or sneeze, transmit the disease vectors 5 , 16 and may be significant contributors to the overall disease load. 17 Consequently, a few recent studies have specifically studied the transmission during talking as well.…”
Section: Introductionmentioning
confidence: 99%